Laporan akhir penyelidikan “Protection of wild animals in Malaysia: enforcement of existing laws and implications’ / Hariati Mansor, Noraziah Abu Bakar and Rozlinda Abdullah - Mansor, Hariati; Abu Bakar, Noraziah; Abdullah, Rozlinda (2006)
This research aims to explore the laws on the protection of wildlife in particular wild life animals. As such, the existing legislation on protection of wild life; namely Protection of Wildlife Act 1972 will be closely examined. In addition to that other statutes which deal with enforcement such as Customs Act 1957 and National Parks Act 1980. The research also looks into the problems encountered by the officers when enforcing the law and the relevant departments' actions to overcome such difficulties. Further, the study will delve into the importance and the implications of protection of wildlife in various aspects especially on economic, political and social.